La norma internacional de contabilidad 12-sección 29 NIF y su incidencia en el plano económico de las pequeñas y medianas empresas del cantón Quevedo. año 2012 - Daza Loor, María Alexandra (2013)
In the international field of financial information, the Council of the International Accounting Standards developed and published a separate set of rules of IFRS's comprehensive, only for Small and Medium Enterprises (SME’s) in order to improve transparency and comparability of financial information, in this sense and to be at the forefront of international standards, the Superintendency of Companies of Ecuador, through Resolution SC.ICI.C.P.A.IFRS.G.11.010, in October 2011, issued the IFRS Regulation and ruled that for purposes of registration and preparation of financial statements, will qualify as SME’s to legal entities that meet less than Four Million Total Assets, a Gross Value Lower Annual Sales to Five Million Dollars, and less than 200 workers as employed persons, hence the present investigation was to identify how it influences the International Accounting Standard 12 - Section 29 IFRS Income Tax economically Small and Medium Enterprises of Canton Quevedo 2012; through inductive, analytic and synthetic methods a diagnosis of the current financial and tax status of the selected sampling companies, trying to know the main differences is in the recognition and interpretation of tax and accounting arrangements are made, eventually concluded that very few companies recognize an asset or deferred tax liability, most of these companies maintain their accounting treatment relating to the tax rules, there is even very little interest in implementing this section of the IFRS for SME's; however, it is considered that the normal course of business and ensuring an efficient harmonization and presentation of financial information against the respective control entities and users of information, it is necessary that these accounting adjustments made for the recognition of respective Income Tax as a result of the Tax payable and Deferred Tax .